Biodiesel production from waste sunflower cooking oil as an environmental recycling process and renewable energy - Hossain, A.B.M.S.; Boyce, A.N. (2009)
Comparison of the optimum conditions of alkaline-catalyzed transesterification process for biodiesel production from pure sunflower cooking oil (PSCO) and waste sunflower cooking Oil (WSCO) through transesterification process using alkaline catalysts was studied. To obtain a high quality biodiesel fuel that comply the specification of standard methods (ASTM D 6751 & EN 14214), some important variables such as volumetric ratio, types of reactants and catalytic activities were selected. The highest approximately 99.5 biodiesel yield acquired under optimum conditions of 1:6 volumetric oil-to-methanol ratio, 1 KOH catalyst at 40(sic)C reaction temperature and 320 rpm stirring speed. Result showed that the biodiesel production from PSCO and WSCO exhibited no considerable differences. The research demonstrated that biodiesel obtained under optimum conditions from PSCO & WSCO was of good quality and could be used as a diesel fuel which considered as renewable energy and environmental recycling process from waste oil after frying.